THE MORPHOLOGICAL AQUISITION ON INDONESIAN 3 YEARS OLD CHILDREN - Maitri Rahmadhani (The Seall Journal, 2020)
The children’s language acquisition will always be interesting things to be investigated. This study is focused on the morphological acquisition on children’s language acquisition of 3 years old children. It is the comparison of Indonesian - 3 years oldchildren speakers and English – 3 years old – children speakersviewed in their morphological acquisition. This study uses a qualitative approach with case study method in order to see all the phenomena that exist in the form of language acquisition children aged 3years old at the level of morphology. Data collection techniques are technical documentation and observation with the help of the recorder such as mobile phones and diaries. It is found that Indonesian - 3 years old- children speaker have faster and more complete in the case of morphological acquisition compared to English – 3 years old – children speaker.